Aspek Hukum Platform E-Commerce Dalam Era Transformasi Digital - Tasya Safiranita Ramli; Ahmad M. Ramli; Rika Ratna Permata; Ega Ramadayanti; Rizki Fauzi (BPSDMP Kominfo Jakarta, 2020)
The growth of the Internet in Indonesia is changing so quickly as it progresses, the existence of Internet is attracting interest to facilitate people who have interest in computers. Lately, Internet service users are increasing rapidly, and start to expand widely with changes in the digital transformation era. Advanced information technology has digitized all fields including business (digital revolution era), because it provides practical ease in the dynamic of communication and information. However, in its development has resulted in a negative impact in the realm of information technology relating to the escalation of crime in cyberspace. This research uses qualitative research methods, a normative juridical approach with descriptive of analysis through data collection techniques in the form of online literature studies that produce secondary data sources with three legal materials. The results of the research present a legal protection effort for consumers conducted in a preventative, repressive, solutive and alternative through dispute resolution both litigation and non-litigation. So that the protection of laws against consumers who utilize e-commerce Platform as an alternative means of online shopping can be assured by the legal efforts of the use of regulations governing the electronic trading, especially on e-commerce Platform social media.Perkembangan internet di Indonesia berubah sangat cepat seiring dengan berjalannya waktu. Beberapa waktu ke belakang, eksistensi internet telah menarik minat sebagian masyarakat yang memiliki ketertarikan terhadap komputer. Akhir-akhir ini, pengguna jasa internet meningkat secara pesat dan mulai berkembang secara luas dengan adanya perubahan di era transformasi digital. Teknologi informasi yang semakin maju telah mendigitalisasi semua bidang termasuk bisnis (digital revolution era) sebab memberikan kemudahan secara praktis dalam dinamisnya komunikasi dan informasi. Namun, dalam perkembangannya telah mengakibatkan dampak negatif dalam ranah teknologi informasi berkaitan dengan eskalasi kejahatan di dunia maya. Dalam penelitian digunakan metode penelitian kualitatif dengan pendekatan yuridis normatif yang bersifat deskriptif analisis melalui teknik pengumpulan data berupa kajian literatur secara daring yang menghasilkan sumber data sekunder dengan tiga bahan hukum. Hasil penelitian menghadirkan upaya perlindungan hukum bagi konsumen yang dilakukan secara preventif, represif, protektif, solutif, dan alternatif melalui penyelesaian sengketa, baik jalur litigasi maupun nonlitigasi sehingga perlindungan hukum terhadap konsumen yang memanfaatkan platform e-commerce sebagai sarana alternatif dalam berbelanja online dapat terjamin dengan adanya upaya hukum dari pemanfaatan regulasi yang mengatur tentang perdagangan elektronik khususnya pada platform e-commerce.